Concurrent validity of the non-exercise based VO2max prediction equation using percentage body fat as a variable in asian Indian adults - Shenoy Shweta; Tyagi Bhupinder S; Sandhu Jaspal S (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology, 2012)
Abstract Background Aerobic capacity (VO2max) is highly dependent upon body composition of an individual and body composition varies with ethnicity. The purpose of this study was to check the concurrent validity of the non-exercise prediction equation developed by Jackson and colleagues (1990) using percentage body fat as a variable in Asian Indian adults. Methods One hundred twenty college-aged participants (60 male, 60 female, mean age 22.02 ± 2.29 yrs) successfully completed a maximal graded exercise test (GXT) on a motorized treadmill to assess VO2max. VO2max was then estimated by the non-exercise prediction equation developed by Jackson and colleagues (1990) using percentage body fat. Percentage body fat was calculated by three different models (Sandhu et al’s fat mass equation, Durnin-womersley’s 4 site percentage body fat and Jackson & Pollock’s 4 site percentage body fat) and was used in the above equation. The results of VO2max obtained using “gold standard” treadmill methods were then compared with the three results of VO2max obtained by Jackson et al’s equation (using three different models to calculate percentage body fat) and it was determined which equation is best suited to determine percentage body fat and in turn VO2 max for Indian population. Results Jackson et al’s prediction equation overpredicts VO2max in Asian Indian subjects who have a lower VO2max (33.41 ± 14.39 ml/kg/min) than those reported in other age matched populations. percentage body fats calculated by the three equations were significantly different and the correlation coefficient (r) between VO2max calculated by Jackson and colleagues (1990) using Sandhu et al’s equation for percentage body fat with VO2 max calculated using treadmill (gold standard) (r = .817) was found slightly more significantly correlated than the other two equations and was not statistically different from the measured value. Conclusions This study proves that VO2max equation using Sandhu et al’s model for percentage body fat yields more accurate results than other studied equations in healthy college-aged participants in India.